Levels and Clinical Significance of Regulatory B Cells and T Cells in Acute Myeloid Leukemia. (6th October 2020) - Dong, Qiaofeng; Li, Guosheng; Fozza, Claudio; Wang, Shuli; Yang, Shuhuan; Sang, Yuqi; Liu, Xinguang; Chen, Chunyan
Abstract : Acute myeloid leukemia (AML) is a heterogeneous hematological malignancy, whose immunological mechanisms are still partially uncovered. Regulatory B cells (Bregs) and CD4+ regulatory T cells (Tregs) are subgroups of immunoregulatory cells involved in modulating autoimmunity, inflammation, and transplantation reactions. Herein, by studying the number and function of Breg and Treg cell subsets in patients with AML, we explored their potential role in the pathogenesis of AML. Newly diagnosed AML patients, AML patients in complete remission, and healthy controls were enrolled. Flow cytometry was used to detect percentages of Bregs and Tregs. ELISA was conducted to detect IL-10 and TGF- β in plasma. The mRNA levels of IL-10 and Foxp3 were measured with RT-qPCR. The relationship of Bregs and Tregs with the clinicopathological parameters was analyzed. There was a significant reduction in the frequencies of Bregs and an increase of Tregs in newly diagnosed AML patients compared with healthy controls. Meanwhile, patients in complete remission exhibited levels of Bregs and Tregs comparable to healthy controls. Furthermore, compared with healthy controls and AML patients in complete remission, newly diagnosed AML patients had increased plasma IL-10 but reduced TGF- β . IL-10 and Foxp3 mRNA levels were upregulated in the newly diagnosed AML patients. However, there were no significant differences in IL-10 and Foxp3 mRNA levels between patients in complete remission and healthy controls. Bregs and Tregs have abnormal distribution in AML patients, suggesting that they might play an important role in regulating immune responses in AML.